The Brandon mathematical model describing the effect of calcination and reduction parameters on specific surface area of ex-ADU UO₂ powders - Nguyen , Trong Hung; Le, Ba Thuan (Nuclear Science and Technology, 2016)
The report “Brandon mathematical model describing the effect of calcination and reduction parameters on speciﬁc surface area of UO2 powders” [14] has built up a mathematical model describing the effect of the fabrication parameters on SSA (Specific Surface Area) of ex-AUC (Ammonium Uranyl Carbonate) UO2 powders. In the paper, the Brandon mathematical model that describe the relationship between the essential fabrication parameters [reduction temperature (TR), calcination temperature (TC), calcination time (tC) and reduction time (tR)] and SSA of the obtained ex-ADU (Ammonium Di-Uranate) UO2 powder product has established. The proposed model was tested with Wilcoxon’s rank sum test, showing a good agreement with the experimental parameters. The proposed model can be used to predict and control the SSA of ex-ADU UO2 powders